Determinación de factores de patogenicidad en cepas de Campylobacter coli y Campylobacter jejuni quinolona resistentes provenientes de niños de entidades de Salud Pública y Centros Infantiles Municipales de Loja - Lojan Ordoñez, Amada Belen (2018)
Abstract:Campylobacter is an emerging enteropathogen and potential zoonotic agent that causes most cases of gastroenteritis, so that the disease occurs this pathogen has several mechanisms of pathogenicity. The purpose of the present project was to determine the adhesion capacity of Campylobacter spp. To intestinal cells, which allows it to remain in the intestine for the subsequent invasion of the digestive tract. We used 18 strains of C. coli and C. jejuni previously isolated from faecal samples of children between 0 to 14 years of maternal and child care centers and public hospitals in the city of Loja. For the characterization of adhesion capacity HEp -2 cells were used, performing in vitro tests and quantifying the number of bacteria adhered after 3 hours of incubation. The results revealed a high percentage of adherence in a strain from the Isidro Ayora Hospital and therefore, according to the criteria of Fernández (1996), it was the only one that was considered adherent.